Synergistic degradation of polyethylene by a restructured bacterial consortium isolated from marine plastic debris - Zhen Rong; Jun-Qing Chen; Yue-Hong Wu; Xue-Wei Xu (Water Research, 2027)

Root accumulation and efficient translocation of steroids in mangrove plants: Implications for an overlooked coastal reservoir - Ji-Xun Chen; Nian-Nian Wu; Shan Liu; Yuan Liu; Qin-Ge Zhou; Qing-Song Yang; Juan Ling; Xiao-Fang Huang; Yan-Kuan Tian; Chang-Gui Pan; Xiang-Rong Xu (Marine Pollution Bulletin, 2026)

Extracellular polymeric substances: overlooked contributors to soil organic carbon persistence - Yichao Wu; Yuwei Yi; Minsu Kim; Samuel Bickel; Ming Zhang; Ke Dai; Chunhui Gao; Chenchen Qu; Chuisi Kong; Mengxi Feng; Ke-Qing Xiao; Hans-Curt Flemming; et al. (Soil Biology and Biochemistry, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Novel prenylated diketopiperazines with anti-osteoclastogenic activity from the deep-sea-derived Penicillium limosum ZEN48 - Yong Zhang; Yan-Qing Guo; You Li; Zheng-Biao Zou; Zhe-Wen Chen; Rong Zhao; Robert J. Capon; Tai-Zong Wu; Chun-Lan Xie; Xian-Wen Yang (Marine Life Science & Technology, 2026)
A systematic chemical investigation of the deep-sea-derived fungus Penicillium limosum ZEN48 resulted in the isolation of four new indole-diketopiperazine alkaloids, limopiperazines A–D ( 1 – 4 ), alongside 16 known analogues ( 5 – 20 ). The structures of the new compounds were determined through comprehensive spectroscopic analysis, quantum chemical calculations, X-ray crystallography, and biogenetic considerations. Limopiperazine C ( 3 ) potently inhibited osteoclast differentiation and disrupted actin ring formation. Integrated RNA sequencing, RT-qPCR and molecular docking revealed that limopiperazine C exerts the anti-osteoclastogenic effect by modulating the ferroptosis signaling pathway via targeting heme oxygenase-1 (Hmox-1), positioning it as a promising lead compound for developing anti-osteoporotic agents.

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Bioinspired interfacial anchoring enables durable ultra-black photothermal coatings based on silica-coated carbon nanotubes - Jian Li; Yan Wang; Xiaolong Wu; Chao Li; De-Rong Sun; Peng Wang; Zimu Li; Xue-Qing Liu (Chemical Engineering Journal, 2026)

Integrating machine learning and prioritization to decipher the partitioning and risk of tire-derived chemicals in highly populated coastal regions - Nian-Nian Wu; Yuan Liu; Shan Liu; Ji-Xun Chen; Qin-Ge Zhou; Xiang-Rong Xu; Qing-Song Yang; Juan Ling; Jian-Liang Zhao (Water Research, 2026)

FabH (β-Ketoacyl-ACP Synthase III) -- Promising Novel Antibacterial Target and Its Inhibitors - Gui-Wen Li; Qing-Yun Rong; Wen Zhang; Guo-Wu Rao; Quan Zheng (Medicinal Chemistry Research, 2026)

Decoding microglial metabolic cell death and PANoptosis hub genes in subacute phase of traumatic brain injury: a multi-omics and experimental validation study - Zhe Wu; Bao-ya Yang; Jin-qing Lai; Shi-hong Lin; Long Lin; Jian-long Chen; Jia-xiang Pan; Yao-xin Ruan; Xiang-rong Chen (Apoptosis, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Mechanoluminescent Janus architecture for stimulus-responsive photodynamic therapy - Rong-Kai Du; Xu-Lin He; Qing-Qing Jin; Hong Liang; Tai-Zhong Xiao; Lei Zhong; Jun-Cheng Zhang; Tian-Ying Sun; Lei Zhou; Ming-Mei Wu (Chemical Engineering Journal, 2026)

Quercetin Alleviates Postoperative Cognitive Dysfunction of Aged Mice by Regulating Microglial Polarization through Inducing miR-379-5p RNA Modification - Shu Rong Li; Long Wang; Yi Wei Li; Yi Xiao Li; Ren Wei Li; Zhi Fang Zhuo; Qing Hua Wu (Molecular Neurobiology, 2026)

Significant generational effects of tetracyclines upon the promoting plasmid-mediated conjugative transfer between typical wastewater bacteria and its mechanisms - Lingling Rong; Baoyin Zhang; Hongmu Qiu; Hailin Zhang; Jiayin Yu; Qing Yuan; Ligui Wu; Hong Chen; Yuanmin Mo; Xiaoming Zou; Xubiao Luo (Water Research, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Metallurgical organic pollutants assisted source apportionment of mobile heavy metals on artisanal non-ferrous metal processing contamination - Li-Rong Liu; Junyao Yan; Lei Xiang; Ting Liu; Ye Xiao; Wen-Shen Liu; Wen-Jun Wu; Ping Li; Miaoyue Zhang; Yuan-Qing Chao; Ye-Tao Tang; Rong-Liang Qiu (Journal of Hazardous Materials, 2025)

Integrated Geology-Geophysics Exploration of Rare Metal Deposits in the Yidun Island Arc Collisional Orogen - Rong Yang; Yu Peng; Li Qing; Qian-kun Liu; Xue-feng Hao; Han Wu; Jun-bo Fan; Hong-juan Chen; Tao Yang (Applied Geophysics, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Degradation of polyethylene by three bacteria isolated from coastal beach - Jun-Qing Chen; Zhen Rong; Dao-Qiong Zheng; Yue-Hong Wu; Xue-Wei Xu (Environmental Research, 2025)

Neuroprotective lindenane sesquiterpenoids from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Shan-Rong Luo; Qian-Qing Liu; Rui-Si Tang; Ning-Yu Chen; Di Luo; Lu Guo; Jia Li; Rui Wu; Zha-Jun Zhan (Phytochemistry, 2025)

Explicit backbone curve prediction of corroded reinforced concrete columns using simulated annealing-optimized genetic programming - Le-Rong Wang; Qing-Feng Liu; Bo Wu; Xin-Yu Zhao (Engineering Structures, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Atmospheric nitrogen deposition has minor impacts on the abundance and diversity of arbuscular mycorrhizal fungi and their contribution to soil carbon stock in tropical forests - Andi Li; Peter Meidl; Senhao Wang; Bo Tang; Matthias C. Rillig; Guangcan Yu; Jing Chen; Rongzhen Liu; Zhiyang Lie; Anchi Wu; Lili Rong; Cheng Peng; et al. (Soil Biology and Biochemistry, 2025)

Contamination, multimedia partitioning, and priority list of steroids and their metabolites in coastal regions of the Greater Bay Area, China - Qin-Ge Zhou; Shan Liu; Yuan Liu; Nian-Nian Wu; Qing-Song Yang; Heng-Xiang Li; Xiang-Rong Xu; Juan Ling (Process Safety and Environmental Protection, 2025)

Unravelling degradation mechanisms of anion exchange membrane direct ammonia fuel cells via distribution of relaxation times - Wenzhi Li; Qing Wang; Yun Liu; Lizhen Wu; Zhefei Pan; Rong Chen; Liang An (Chemical Engineering Journal, 2025)

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

Ground ozone rise during the 2022 shanghai lockdown caused by the unfavorable emission reduction ratio of nitrogen oxides and volatile organic compounds - Qian Wang; Yuewu Li; Fangqian Zhong; Wanqi Wu; Hongliang Zhang; Rong Wang; Yusen Duan; Qingyan Fu; Qing Li; Lin Wang; Shaocai Yu; Abdewahid Mellouki; et al. (Atmospheric Environment, 2025)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Composition of Sphagnum palustre L. extracts using different extraction methods - Zhi Wu; Zheng-Yi Hong; Yang Xu; Dai-Rong Wang; Qing-Bin Han; Ping Liu; Xiao-Rong Liu; Lan-Yue Zhang (Natural Product Research, 2024)

Circ-IP6K2 suppresses tumor progression by modulating the miR-1292-5p/CAMK2N1 signal in clear cell renal cell carcinoma - Jian-ying Tang; Lu Yang; Qing-Jian Wu; Ying Yang; Yuan-Yuan Su; Yi-Rong Chen; Jiao Mu (Functional & Integrative Genomics, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Synergistic driving effects of risk factors on human brucellosis in Datong City, China: A dynamic perspective from spatial heterogeneity - Li Shen; Ming-hao Sun; Wen-tao Ma; Qing-wu Hu; Chen-xi Zhao; Zu-rong Yang; Cheng-hao Jiang; Zhong-jun Shao; Kun Liu (Science of The Total Environment, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

Differences in particulate matter retention and leaf microstructures of 10 plants in different urban environments in Lanzhou City - Rong Huang; Qing Tian; Yue Zhang; Zhini Chen; Yonghua Wu; Zizhen Li; Zebin Wen (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Investigating the thermal conductivity and flame-retardant properties of BN/MoS2/PCNF composite film containing low BN and MoS2 nanosheets loading - Lei Yang; Wei Xu; Xiaolong Shi; Menglin Wu; Ziyi Yan; Qing Zheng; Gongneng Feng; Li Zhang; Rong Shao (Carbohydrate Polymers, 2023)

Transformation of cognition from mechanical to biological aqueous outflow pump may be a breakthrough in solving the problem of intraocular pressure regulation in glaucoma - Shen Wu; Chen Xin; Wei Zhu; Yue Wan; Qing Sang; Rong Du; Jian Wu; Jin Wang; Ningli Wang (Science China Life Sciences, 2023)

Sunshine duration and risks of schizophrenia hospitalizations in main urban area: Do built environments modify the association? - Li Liu; Qing Wu; Xuanxuan Li; Rong Song; Ning Wei; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Amycolatolides A and B: Two new secondary metabolites from the lichen-derived actinomycete Amycolatopsis sp. YIM 130923 - Qing-Rong Yang; Yi Jiang; Chuan-Sheng Liu; Tang-Chang Xu; Rong Huang; Shao-Hua Wu (Phytochemistry Letters, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

An antioxidant lignan glycoside and triterpenoid saponins from the leaves of Synsepalum dulcificum - Xin-Peng Li; Jun-Fei Wang; Rong Huang; Tang-Chang Xu; Si-Si Liu; Qing-Rong Yang; Shao-Hua Wu (Phytochemistry Letters, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Ambient air pollutants increase the risk of immunoglobulin E–mediated allergic diseases: a systematic review and meta-analysis - Hua Wang; Xian-Bao Li; Xiu-Jie Chu; Nv-Wei Cao; Hong Wu; Rong-Gui Huang; Bao-Zhu Li; Dong-Qing Ye (Environmental Science and Pollution Research, 2022)

Cassiterite oxygen isotopes in magmatic-hydrothermal systems: in situ microanalysis, fractionation factor, and applications - Yang Li; Sheng He; Rong-Qing Zhang; Xian-Wu Bi; Lian-Jun Feng; Guo-Qiang Tang; Wen-Zhong Wang; Fang Huang; Xian-Hua Li (Mineralium Deposita, 2022)

Growth influence of juvenile golden trout (Oncorhynchus mykiss) in different osmotic conditions: implications for tissue histology, biochemical indicators, and genes transcription involved in GH/IGF system - Baoliang Bi; Yu Gao; Dan Jia; Lingfu Kong; Yanhua Su; Hua Rong; Xiangwei Wu; Xiaowen Wang; Zhuoyong Hu; Qing Hu (Fish Physiology and Biochemistry, 2021)

Carnosic acid alleviates depression-like behaviors on chronic mild stressed mice via PPAR-γ-dependent regulation of ADPN/FGF9 pathway - Xiao-qing Wang; Ya-hui Tang; Gui-rong Zeng; Li-feng Wu; Ying-jun Zhou; Ze-neng Cheng; De-Jian Jiang (Psychopharmacology, 2021)

Correlation of exosomal microRNA clusters with bone metastasis in non-small cell lung cancer - Xiao-Rong Yang; Can Pi; Ruoying Yu; Xiao-Jun Fan; Xiao-Xiao Peng; Xu-Chao Zhang; Zhi-Hong Chen; Xue Wu; Yang Shao; Yi-Long Wu; Qing Zhou (Clinical & Experimental Metastasis, 2021)
20–40% of lung cancer patients develop bone metastasis (BM) with significantly decreased overall survival. Currently, BM is mainly diagnosed by computerized tomography (CT) scan or magnetic resonance imaging (MRI) when symptom develops. Novel biomarkers with higher prediction value of BM are needed. Plasma-derived exosomal microRNAs had been isolated and sequenced of total 30 non-small cell lung cancer (NSCLC) patients including 16 with bone metastasis and 14 without bone metastasis. Hierarchical clustering based on the total miRNA profile can clearly separate cancer patients and healthy individuals (H), but not patients with (BM +) or without (BM−) BM. Weight Co-expression network of miRNAs (WGCNA) analyses identified three consensus clusters (A, B, C) of highly correlated miRNAs, among which cluster B (144 miRNAs) showed significantly differential expression in lung cancer patients, especially in BM + group. Pathway analysis of cluster B miRNAs revealed enrichment in metabolic pathways that may involve in preconditioning of the metastatic niche. Three differentially expressed miRNAs between BM + and BM− patients within cluster B were identified as miR-574-5p, a suppressor of Wnt/β-catenin pathway, was down-regulated, while miR-328-3p and miR-423-3p, two activators of the same pathway, were up-regulated in BM + patients. Cluster A miRNAs (n = 49) also showed trend of upregulation in BM + patients. Interestingly, pathway analysis indicated that 43 of them are associated with chromosome14, which has been suggested to promote epithelial-mesenchymal transition (EMT) and bone metastasis.

Tectochrysin increases stress resistance and extends the lifespan of Caenorhabditis elegans via FOXO/DAF-16 - Min Lu; Lin Tan; Xiao-Gang Zhou; Zhong-Lin Yang; Qing Zhu; Jian-Ning Chen; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Seasonal variations of organic carbon and nitrogen in the upper basins of Yangtze and Yellow Rivers - Xiang-ying Li; Yong-jian Ding; Tian-ding Han; Jian-zhong Xu; Shi-chang Kang; Qing-bai Wu; Mika Sillanpää; Zhong-bo Yu; Cong-rong Yu (Journal of Mountain Science, 2017)

Association between hyperhomocysteinemia and stroke with atherosclerosis and small artery occlusion depends on homocysteine metabolism-related vitamin levels in Chinese patients with normal renal function - Guan-Hui Wu; Fan-Zhen Kong; Xiao-Feng Dong; De-Feng Wu; Qian-Zhu Guo; Ai-Rong Shen; Qing-Zhang Cheng; Wei-Feng Luo (Metabolic Brain Disease, 2017)

A novel non-ATP competitive FGFR1 inhibitor with therapeutic potential on gastric cancer through inhibition of cell proliferation, survival and migration - Jianzhang Wu; Xiaojing Du; Wulan Li; Yangyang Zhou; Encheng Bai; Yanting Kang; Qiuxiang Chen; Weitao Fu; Di Yun; Qing Xu; Peihong Qiu; Rong Jin; et al. (Apoptosis, 2017)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Comparison of seven colchicine-induced tetraploid clones with their original diploid clones in purple coneflower (Echinacea purpurea L.) - Rong Chen; Wei-zhen Jiang; Qing-ling Li; Xin-lian Li; Xiao-lu Chen; Yue-sheng Yang; Hong Wu (Euphytica, 2016)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)

Isolation and characterization of microsatellite loci in the Ussuri mamushi (Gloydius ussuriensis) - Rong-Fang Wang; Yan-Qing Wu; Zhe Liu; Yan-Fu Qu (Conservation Genetics Resources, 2014)

Microsatellite primer development for the king ratsnakes Elaphe carinata (Colubridae) - Yan-Qing Wu; Rong-Fang Wang; Long-Hui Lin; Yan-Fu Qu (Conservation Genetics Resources, 2014)

Characterization of eubacterial and archaeal community diversity in the pit mud of Chinese Luzhou-flavor liquor by nested PCR–DGGE - Xiao-Fei Ding; Chong-De Wu; Li-Qiang Zhang; Jia Zheng; Rong-Qing Zhou (World Journal of Microbiology and Biotechnology, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

IFNG polymorphisms are associated with tuberculosis in Han Chinese pediatric female population - Chen Shen; Wei-Wei Jiao; Wei-Xing Feng; Xi-Rong Wu; Jing Xiao; Qing Miao; Lin Sun; Bin-Bin Wang; Jing Wang; Fang Liu; Dan Shen; A-Dong Shen (Molecular Biology Reports, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

Effects of Schisandra sphenanthera extract on the blood concentration of tacrolimus in renal transplant recipients - Hua-Wen Xin; Qing Li; Xiao-Chun Wu; Yan He; Ai-Rong Yu; Lei Xiong; Ying Xiong (European Journal of Clinical Pharmacology, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Lingo2 variants associated with essential tremor and Parkinson’s disease - Yi-Wen Wu; K. M. Prakash; Tian-Yi Rong; Hui-Hua Li; Qin Xiao; Louis C. Tan; Wing-Lok Au; Jian-qing Ding; Sheng-di Chen; Eng-King Tan (Human Genetics, 2011)

Cytological and RAPD data revealed genetic relationships among nine selected populations of the wild bramble species, Rubus parvifolius and R. coreanus (Rosaceae) - Xiao-rong Wang; Yuan Liu; Bi-feng Zhong; Xiao-li Dong; Qing Chen; Wu-feng Xia; Hanwu Zhang; Hao-ru Tang (Genetic Resources and Crop Evolution, 2010)

Relationships between thiopurine S-methyltransferase polymorphism and azathioprine-related adverse drug reactions in Chinese renal transplant recipients - Hua-Wen Xin; Hui Xiong; Xiao-Chun Wu; Qing Li; Lei Xiong; Ai-Rong Yu (European Journal of Clinical Pharmacology, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

A Novel Glycosylphosphatidylinositol-Anchored Alkaline Phosphatase Dwells in the Hepatic Duct of the Pearl Oyster, Pinctada fucata - Li-Ping Xie*; Yuan-Tai Wu*; Yi-Ping Dai; Qing Li; Rong-Qing Zhang (Marine Biotechnology, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Apelin suppresses apoptosis of human osteoblasts - Hui Xie; Ling-Qing Yuan; Xiang-Hang Luo; Jiao Huang; Rong-Rong Cui; Li-Juan Guo; Hou-De Zhou; Xian-Ping Wu; Er-Yuan Liao (Apoptosis, 2007)

Novel CACNA1S mutation causes autosomal dominant hypokalemic periodic paralysis in a Chinese family - Qiufen Wang; Mugen Liu; Chunsheng Xu; Zhaohui Tang; Yuhua Liao; Rong Du; Wei Li; Xiaoyan Wu; Xu Wang; Ping Liu; Xianqin Zhang; Jianfang Zhu; et al. (Journal of Molecular Medicine, 2005)

Genetic Conservation of Hemagglutinin Gene of H9 Influenza Virus in Chicken Population in Mainland China - Jin-Hua liu; Katsunori Okazaki; Aaron Mweene; Wei-Min Shi; Qing-Min Wu; Jing-Liang Su; Guo-Zhong Zhang; Gui-Rong Bai; Hiroshi Kida (Virus Genes, 2004)